Multitemporal analysis of deforestation and burns in the Itacaiúnas sub-basin, Maraba - Para (Research, Society and Development, 2021)
Changes in landscapes due to deforestation and burning are the consequence of anthropic actions that cause damage to the environment, and the use of GIS technologies favors the monitoring of these changes. The objective of this research was to analyze, in a quantitative way, the evolution of deforestation and fires in the Itacaiúnas River sub-basin, with a time frame ranging from 2006-2017, with triennial intervals. To prepare the thematic maps, geographic data were collected from INPE, DETER, PRODES and BDQUEIMADAS. The acquired data were treated using the Kernel Density tool in QGis software. The analysis indicated that the triennium 2006-2008, recorded greater extension in deforestation (n = 162.10 km2) and fires (n = 5,586) differently from the years 2012-2014 with lower occurrences in these aspects (deforestation, n = 15.93 km2; fires, n = 595 focuses). The 10 municipalities of the sub-basin presented relevant averages for deforestation (n = 23.0 km2/year) and fires (n = 828.8 focus/year), with Marabá standing out for manifesting the largest deforested area and fires focus ( = 106.4±95.1). Lower values of deforestation were found in Curionópolis (  = 1.1±1.2), while Sapucaia indicated the smallest fires ( = 32.0±28.4). With these data one can identify the main capitals involved in these two actions in Marabá: cattle ranching, because between 2009-2011, this activity suffered an increase equal to 32%. As deforestation is frequent in this municipality, it is advisable to use as pastureland, those areas that no longer have vegetation cover to mitigate deforestation.